Competition law's inclusion of public interest considerations in mergers and beyond: a potential paradox? - Meyer, Nicholas (Department of Commercial Law, 2017)
The inclusion of public interest considerations in competition law legislation has been controversial, dividing policy makers and economists alike. Debate has focused on the practical application of these public interest concerns when a merger is proposed, or when prohibited conduct is implicated. The uncertainty involved has had to be addressed by the competition authorities in recent years when dealing with high profile mergers and excessive pricing cases. This has necessitated development in somewhat unchartered legal terrain: the incorporation into competition policy of traditionally non-competition objectives. The traditional purpose of competition law has primarily been protecting and enhancing consumer welfare. Attempting to reconcile this objective with public interest considerations, which are now statutorily enshrined, presents significant challenges. However, South Africa's pressing economic redistributive justice needs provided compelling motivation for the legislature including public interest considerations in competition law, and authorities must remain cognizant of this. This paper critically considers whether it is appropriate for competition authorities to address welfare and public interest concerns, by analysing significant merger and prohibited conduct cases involving public interest considerations. A comparison into international approaches and trends in including public interest factors in competition control serves to provide global context. Furthermore, this paper interrogates the legitimacy of intervening in the public interest, whilst examining the tension between efficiency and equity.